Factors of lumbosacral radiculopathy chronicity - L. A. Dziak; O. O. Shulha; V. M. Suk (Zaporožskij Medicinskij Žurnal)
Assessment of chronic factors of acute lumbosacral radiculopathy is an urgent problem due to the disease impact on the quality of life of patients, possible loss of work capacity and disability.